2005
DOI: 10.1890/04-1677
|View full text |Cite
|
Sign up to set email alerts
|

Carbon, Nitrogen, and Phosphorus Accumulation in Floodplains of Atlantic Coastal Plain Rivers, Usa

Abstract: Net nutrient accumulation rates were measured in riverine floodplains of the Atlantic Coastal Plain in Virginia, Maryland, and Delaware, USA. The floodplains were located in watersheds with different land use and included two sites on the Chickahominy River (urban), one site on the Mattaponi River (forested), and five sites on the Pocomoke River (agricultural). The Pocomoke River floodplains lie along reaches with natural hydrogeomorphology and on reaches with restricted flooding due to channelization and leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
147
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 199 publications
(165 citation statements)
references
References 52 publications
12
147
2
Order By: Relevance
“…In other studies, poor connectivity and strong fragmentation of floodplain result in a lower rate of mineral sedimentation and P accumulation [104]. In this study agricultural intensification shifted the arable land into larger fields, which equalized the conditions and had negative impacts on species diversity, as also found by Harms et al [105].…”
Section: What Is the Ecological Relevance Of The Observed Trends In Tsupporting
confidence: 75%
“…In other studies, poor connectivity and strong fragmentation of floodplain result in a lower rate of mineral sedimentation and P accumulation [104]. In this study agricultural intensification shifted the arable land into larger fields, which equalized the conditions and had negative impacts on species diversity, as also found by Harms et al [105].…”
Section: What Is the Ecological Relevance Of The Observed Trends In Tsupporting
confidence: 75%
“…At the reach scale, TOC and TN exchange between the main channel and its adjacent floodplain plays a key role in the ecological functioning (Junk, 1999;Robertson et al, 1999;Tockner et al, 1999;Tockner at al., 2000;Thoms, 2003;Knosche, 2006;Preiner et al, 2008). Previous research has shown how human-induced changes at the basin and reach scale have decreased the potential of riverine floodplains to act as sediment-associated nutrient sinks (Noe and Hupp, 2005;Owens et al, 2005;Pierce and King, 2008;Cabezas et al, 2009;Cabezas and Comin, 2010). To accomplish knowledge-based management and restoration strategies at specific river reaches, TOC and TN deposition patterns must be properly understood.…”
Section: Introductionmentioning
confidence: 99%
“…scale by channel-floodplain geomorphology, which promotes spatial variability on sedimentation load and patterns for a given river section during a specific flood event (Hupp, 2000;Noe and Hupp, 2005;Piégay et al, 2008). At this scale, previous studies have indicated that distance from the main channel exerts more influence on spatial variability of overbank sedimentation than downstream variation (Walling and He, 1998;Middelkoop and Asselman, 1998;Thonon et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We did not observe significant erosion at any plot. It should be noted that N sedimentation is controlled by organic matter accumulation and hence is not equal to available N. Because of the linear relationship between N and organic C content of deposited sediments (C/N ratio of fresh sediments was around 11 in all FPZs, Weibel, 2011), we assume as in earlier studies (Stoeckel and Miller-Goodman, 2001;Noe and Hupp, 2005) that N is dominantly organic and has first to be mineralized. Furthermore, this low C/N ratio compared to that of the top 10 cm (C/N ratio = 15, Table 1) suggests that around 30 % of the organic matter in the newly deposited sediments is easily degradable.…”
Section: N Balancementioning
confidence: 97%